The Psychological Dimension of Latin American Pentecostalism: A Scoping Review - Almeida, Raul Gomes (International journal of Latin American religions, 2025)
This article presents a scoping review on the psychological dimension of adherence to Pentecostalism in Latin America, analyzing a corpus consisting of 41 articles published in scientific journals from 1990 to 2023. The methodology consisted of identifying, organizing, and synthesizing the main findings in the literature, focusing on themes such as the conversion process, subjective transformations in adherence, suffering and healing experiences, community experiences, and the construction of religious belonging. The analysis reveals that Pentecostal practices and symbols significantly impact the subjectivity of adherents, influencing their way of interpreting the world and their social relationships. The review highlights the complexity of the subjective experiences related to Pentecostalism, emphasizing the importance of understanding them within the specific cultural, political, and socioeconomic contexts of Latin American reality.